Dynamics of Political Communication amid a Global Health Crisis: Government Response and Public Response - Amalia, Nadia; Joshua, Wang; Barra, Ling (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
The global health crisis caused by the COVID-19 pandemic has changed the dynamics of political communication in various countries. Governments around the world are faced with unprecedented communications challenges, where rapid and effective decisions are urgently needed to address the spread of the virus. However, the effectiveness of political communication is often hampered by lack of information, misunderstanding and public distrust. This research aims to analyze how the government communicates with the public during a health crisis and how the public responds to this communication. The primary goal is to identify effective strategies and uncover communication gaps that can serve as valuable lessons for future crises. The method used in this research is content analysis from various news sources, government reports and social media. In addition, respondents were surveyed to measure public perceptions and responses to government communications. The research results show significant variation in the effectiveness of communication strategies between countries. Countries with open, transparent and consistent communication tend to experience higher levels of public compliance and more controlled spread of the virus. Meanwhile, countries with sporadic and ambiguous communications have had difficulty managing the pandemic and faced more excellent public resistance. This research concludes that success in managing a health crisis depends not only on the policies taken but also on how the government communicates with the public. Transparency, consistency and continuity in communications have proven critical in building public trust and supporting pandemic mitigation efforts. This research provides insights that can help policymakers improve communication strategies in the future.